Odor from anaerobic digestion of swine slurry: influence of pH, temperature and organic loading (Scientia Agricola, 2014)
Farm slurry management from storage and/or treatment is the main source of odors from swine production, which are determined by factors such as operational variations (organic loading), cleaning of facilities and animal diet (pH) or environmental conditions (temperature). The aim of this study was to evaluate the influence of pH, temperature and organic loading on odor generation during anaerobic digestion of swine slurry. The methodology employed batch experimental units under controlled pH (6.0, 6.5, 7.0 and 8.0) and temperature (20, 35 and 55 °C) conditions. Additionally, an Upflow Anaerobic Sludge Blanket (UASB) system was operated under two Organic Loading Rate (OLR) conditions as Chemical Oxygen Demand (COD) (Phase I: 0.4 g L-1 d-1 of COD, Phase II: 1.1 g L-1 d-1 of COD). Odor (batch and UASB reactor) was evaluated by detection and recognition threshold as Dilution Threshold (D-T). Acidic conditions (pH 6.0) and thermophilic temperatures (55 °C) increased odors (1,358 D-T) and acidified the system (Intermediate/Total Alkalinity ratio (IT/TA): 0.85) in batch experiments. Increasing OLR on UASB reactor reduced odors from 6.3 to 9.6 D-T d-1 due to an increase in the production of biogas (0.4 to 0.6 g g-1 COD removed of biogas).